Konsep Eros Dan Agape Dalam Kehidupan Manusia Menurut Anders Nygren - Herlambang, Paulinus; Fransiskus Borgias M (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
Eros, as love associated with self-desire and self-gratification, contrasts with Agape, which is genuine love prioritizing the welfare of others above oneself. This article employs a literary analysis method to explore how these two concepts influence and interact within the dynamics of human relationships, both spiritually and interpersonally. The findings indicate that a profound understanding of Eros and Agape can enrich and deepen the meaning of authentic human relationships, offering a fresh perspective on how love can transform and affirm human dignity in the context of relationships with others and with God. Insights from Eros and Agape contribute to expanding our understanding of love in human life and its relevance in broader social and spiritual contexts